How can central banks help mitigate climate change? A money view perspective on green central banking - Jakob Vestergaard (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2022)
Central banks can potentially influence the investment decisions of private financial institutions, which in turn will create incentives towards green technology adoption and development of lower emission business models. This paper examines how central bankers are engaging with the green transition agenda. To guide the efforts, the paper mobilizes the Money View literature. This enables a comparative assessment of different monetary policy options. The main finding is that a promising way forward for Green Central Banking is to adopt a dual strategy of expanding collateral eligibility through positive screening and widening haircut spreads to change relative incentives in favor of green over brown assets.
Keywords: 330